A systematic review and meta‐ethnographic synthesis of Mindfulness‐based Cognitive Therapy for people with major depression. (15th August 2022) - Williams, Kate; Hartley, Samantha; Langer, Susanne; Manandhar‐Richardson, Mizla; Sinha, Melissa; Taylor, Peter
Abstract: Background: Mindfulness‐based Cognitive Therapy (MBCT) is a relapse‐prevention intervention for people experiencing major depression. Three qualitative meta‐syntheses investigating experiences of taking part in MBCT and/or Mindfulness‐based Stress Reduction (MBSR) across different diagnostic populations reported themes including control, choice, group processes, relationships and struggles. As multiple studies have been published since, we aimed to update, systematically review and synthesize the experiences of participants with depression taking part in MBCT. Methods: Four databases were searched systematically (PsycInfo, Web of Science, Medline and CINAHL) up to and including 12 November 2021. Twenty‐one qualitative studies met the review criteria. All papers were rated as fair using a quality appraisal tool. Meta‐ethnography was applied. Results: Across 21 studies of participants with current or previous depression who had participated in MBCT, three overarching themes were developed: 'Becoming skilled and taking action', 'Acceptance' and 'Ambivalence and Variability'. Participants became skilled through engagement in mindfulness practices, reporting increased awareness, perspective and agency over their experiences. Participants developed acceptance towards their experiences, self and others. There was variability and ambivalence regarding participants' expectations and difficulties within mindfulness practices. Limitations: Many studies were conducted in MBCT‐research centres that may hold conflicts of interest. Many studies did not address the impact of the participant–researcher relationship thus potentially affecting their interpretations. Studies were skewed towards the experiences of female participants. Conclusions: Our findings help to enhance participant confidence in MBCT, alongside understanding the processes of change and the potential for difficulties. MBCT is beneficial and provides meaningful change for many but remains challenging for some.